2016
DOI: 10.1177/1075547016663001
|View full text |Cite
|
Sign up to set email alerts
|

Americans’ Support for NASA’s James Webb Space Telescope

Abstract: This study tested responses to traditional or interactive material about NASA’s James Webb Space Telescope (JWST) project. A total of 660 participants were divided into three groups: a science guide group that viewed an online PDF, an interactive group that viewed a YouTube video and FlyBy simulation, and a control group that received no supporting texts about JWST. Interactive media outperformed traditional texts in increasing levels of support for JWST construction. However, the traditional text and interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…These findings have significant implications not only for astronauts, but for the general public. Research has already demonstrated that interactive experiences with images from space increased people's intention to support and advocate for space project funding (Weber et al, 2016) and that viewing images of beauty in space fosters positive involvement in climate change activism (O'neill & Nicholson-Cole, 2009). Additionally, Smith et al (2011) explain that non-experts actually look at images from space with an eye for beauty and with more emotion than experts looking at these images.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have significant implications not only for astronauts, but for the general public. Research has already demonstrated that interactive experiences with images from space increased people's intention to support and advocate for space project funding (Weber et al, 2016) and that viewing images of beauty in space fosters positive involvement in climate change activism (O'neill & Nicholson-Cole, 2009). Additionally, Smith et al (2011) explain that non-experts actually look at images from space with an eye for beauty and with more emotion than experts looking at these images.…”
Section: Discussionmentioning
confidence: 99%